Rheological and Biological Impact of Printable PCL-Fibers as Reinforcing Fillers in Cell-Laden Spider-Silk Bio-Inks - Schaefer, Natascha; Andrade Mier, Mateo S.; Sonnleitner, David; Murenu, Nicoletta; Ng, Xuen Jen; Lamberger, Zan; Büchner, Margitta; Trossmann, Vanessa T.; Schubert, Dirk W.; Scheibel, Thomas; Lang, Gregor (Small Methods, 2023)
The development of bio-inks capable of being 3D-printed into cell-containing bio-fabricates with sufficient shape fidelity is highly demanding. Structural integrity and favorable mechanical properties can be achieved by applying high polymer concentrations in hydrogels. Unfortunately, this often comes at the expense of cell performance since cells may become entrapped in the dense matrix. This drawback can be addressed by incorporating fibers as reinforcing fillers that strengthen the overall bio-ink structure and provide a second hierarchical micro-structure to which cells can adhere and align, resulting in enhanced cell activity. In this work, the potential impact of collagen-coated short polycaprolactone-fibers on cells after being printed in a hydrogel is systematically studied. The matrix is composed of eADF4(C16), a recombinant spider silk protein that is cytocompatible but non-adhesive for cells. Consequently, the impact of fibers could be exclusively examined, excluding secondary effects induced by the matrix. Applying this model system, a significant impact of such fillers on rheology and cell behavior is observed. Strikingly, it could be shown that fibers reduce cell viability upon printing but subsequently promote cell performance in the printed construct, emphasizing the need to distinguish between in-print and post-print impact of fillers in bio-inks.
CRIS-Team Scopus Importer:2023-07-07
Keywords: bio-inks; bio-printing; biofabrication; composites; fibers; silk